Prognostic value of coronary computed tomography angiography-derived morphologic and quantitative plaque markers using semiautomated plaque software - Baumann, Stefan; Kaeder, Finja; Schoepf, U. Joseph; Golden, Joseph W.; Kryeziu, Philipp; Tesche, Christian; Renker, Matthias; Janssen, Sonja; Weiß, Christel; Hetjens, Svetlana; Schönberg, Stefan; Borggrefe, Martin; et al. (Journal of thoracic imaging, 2021)
Purpose: - In this study, we analyzed the prognostic value of coronary computed tomography angiography-derived morphologic and quantitative plaque markers and plaque scores for major adverse cardiovascular events (MACEs). - Materials and Methods: - We analyzed the data of patients with suspected coronary artery disease (CAD). Various plaque markers were obtained using a semiautomated software prototype or derived from the results of the software analysis. Several risk scores were calculated, and follow-up data concerning MACE were collected from all patients. - Results: - A total of 131 patients (65±12 y, 73% male) were included in our study. MACE occurred in 11 patients within the follow-up period of 34±25 months. - CAD-Reporting and Data System score (odds ratio [OR]=11.62), SYNTAX score (SS) (OR=1.11), Leiden-risk score (OR=1.37), segment involvement score (OR=1.76), total plaque volume (OR=1.20), and percentage aggregated plaque volume (OR=1.32) were significant predictors for MACE (all P≤0.05). Moreover, the difference of the corrected coronary opacification (ΔCCO) correlated significantly with the occurrence of MACE (P<0.0001). The CAD-Reporting and Data System score, SS, and Leiden-risk score showed substantial sensitivity for predicting MACE (90.9%). The SS and Leiden-risk score displayed high specificities of 80.8% and 77.5%, respectively. These plaque markers and risk scores all provided high negative predictive value (>90%). - Conclusion: - The coronary computed tomography angiography-derived plaque markers of segment involvement score, total plaque volume, percentage aggregated plaque volume, and ΔCCO, and the risk scores exhibited predictive value for the occurrence of MACE and can likely aid in identifying patients at risk for future cardiac events.
Gesehen am 14.09.2021